2023
DOI: 10.1111/bdi.13317
|View full text |Cite
|
Sign up to set email alerts
|

Serum angioneurin levels following electroconvulsive therapy for mood disorders

Abstract: ObjectivesThe efficacy of electroconvulsive therapy (ECT) in treating mood disorders (MDs) is hypothesized to be mediated by the induction of neurotrophic factors (denoted “angioneurins”) that trigger neuronal plasticity. This study aimed to assess the effects of ECT on serum angioneurin levels in patients with MD.MethodsA total of 110 patients with MDs including 30 with unipolar depression, 25 with bipolar depression (BD), 55 with bipolar mania (BM), and 50 healthy controls were included in the study. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Surprisingly, however, both pretreatment CT and the early increase in CT seem to represent predictive biomarkers of the clinical response to antidepressants(Phillips et al, 2015) suggesting that various processes can underlie its clinical effectiveness. Neuroplasticity, including the processes of neurogenesis, synaptogenesis, dendrogenesis, gliogenesis, and angiogenesis, has been hypothesised to be the biological mechanism for the effects of ECT on CT (Hellsten et al, 2005; Jaggar et al, 2023; Wennström et al, 2004; Zhang et al, 2023). In particular, animal studies have reported that rats subjected to electroconvulsive stimulation show increased genesis of hippocampal neurons with the potential for long-term survival (Altar et al, 2003; Madsen et al, 2005; Olesen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, both pretreatment CT and the early increase in CT seem to represent predictive biomarkers of the clinical response to antidepressants(Phillips et al, 2015) suggesting that various processes can underlie its clinical effectiveness. Neuroplasticity, including the processes of neurogenesis, synaptogenesis, dendrogenesis, gliogenesis, and angiogenesis, has been hypothesised to be the biological mechanism for the effects of ECT on CT (Hellsten et al, 2005; Jaggar et al, 2023; Wennström et al, 2004; Zhang et al, 2023). In particular, animal studies have reported that rats subjected to electroconvulsive stimulation show increased genesis of hippocampal neurons with the potential for long-term survival (Altar et al, 2003; Madsen et al, 2005; Olesen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, both pretreatment CT and the early increase in CT seem to represent predictive biomarkers of the clinical response to antidepressants (Phillips et al, 2015), suggesting that various processes can underlie its clinical effectiveness. Neuroplasticity, including the processes of neurogenesis, synaptogenesis, dendrogenesis, gliogenesis, and angiogenesis, has been hypothesised to be the biological mechanism for the effects of ECT on CT (Wennström et al, 2004;Hellsten et al, 2005;Jaggar et al, 2023;Zhang et al, 2023). In particular, animal studies have reported that rats subjected to electroconvulsive stimulation show increased genesis of hippocampal neurons with the potential for long-term survival (Altar et al, 2003;Madsen et al, 2005;Olesen et al, 2017).…”
Section: Biological Significance Of Ct Findingsmentioning
confidence: 99%